Global Research Status and Trends of Femoral Neck Fracture Over the Past 27 Years: A Historical Review and Bibliometric Analysis - Peng, Peng; Xiao, Fangjun; He, Xiaoming; Fang, Weihua; Huang, Jiewen; Wang, Bin; Luo, Yiwen; Zhang, Qinwen; Zhang, Ying; He, Wei; Wei, Qiushi; He, Mincong (Frontiers in Surgery, 2022)
Background: Femoral neck fracture (FNF) is a commonly encountered injury in orthopaedic practice, and many studies has been conducted in this field. However, no bibliometric studies regarding the global research trend concerning FNF have been performed. This study aims to analyze the knowledge framework, research hotspots, and theme trends in the field of FNF research. Methods: The scientific outputs related to FNF from 1994 to 2021 were retrieved from the Web of Science Core Collection. Three bibliometric tools were used for this study. The main analyses include publication and citation counts, contributions of countries, institutions, authors, funding agencies and journals, and clustering of keywords. Results: In total, 3553 articles were identified. The annual publication counts of FNF showed an ascending tendency as a whole. The United States has the most prominent contributions, with the most number of publications and the highest H-index. Karolinska Institutet devoted the most in this domain. Professors Bhandari M, Schemitsch EH, Frihagen F, Parker MJ, and Rogmark C were the core authors in this field. The most productive journal was Injury International Journal of the Care of the Injured. Keywords were divided into four clusters: epidemiology and mortality, fracture prevention, internal-fixation and risk factors, and hip replacement. A trend of balanced and diversified development existed in these clusters. Keywords with the ongoing bursts, including “outcome,” “reoperation,” “complication,” “revision,” “displaced intracapsular,” “fracture,” and “adult,” are considered as the research hotspots in the future and deserve more attention. Conclusions: The management of FNF in young patients is drawing more attention from orthopedic surgeons, it is expected that these research topics may continue to be the research hotspots and focus in the near future.